Attitudes towards compulsory vaccination in Italy: Results from the NAVIDAD multicentre study. Issue 23 (31st May 2018) - ,; Castaldi, S.; Di Donna, F.; Di Martino, G.; Genovese, C.; Golfera, M.; Gori, D.; Greco, P.; Loperto, I.; Miduri, A.; Olivero, E.; Prospero, E.; et al.
Highlights: Compulsory vaccination is generally welcome in Italy. Mandatory vaccinations are not affected by social determinants. Confidence in the health system determines the trustworthiness of mandatory vaccination. Abstract: Background: Vaccine hesitancy is a considerable issue in European countries and leads to low coverage rates. After a long debate, Italy has made vaccination mandatory for admission to its schools. Methods: In the NAVIDAD study (a cross-sectional multicentre study), a 63-item questionnaire was administered to 1820 pregnant women from 15 Italian cities. The questionnaire assessed the interviewee's opinion on mandatory vaccines, as well as their socioeconomic status, sources of information about vaccines, confidence in the Italian National Healthcare Service (NHS), and intention to vaccinate their newborn. Results: Information sources play a key role in determining the opinion on restoration of mandatory vaccines; in particular, women who obtained information from anti-vaccination movements are less likely to accept the vaccines (OR: 0.35, 95% CI: 0.21–0.58, p < 0.001). Women who had confidence in healthcare professional information agreed more on mandatory vaccination than did the other women (OR: 2.66, 95% CI: 1.62–4.36, p < 0.001); those who perceived that healthcare professionals have economic interest in child immunization and who declared that healthcare providers inform only on vaccinations benefits not on risks were less likely to agree on compulsory vaccination (OR: 0.66, CI 95%: 0.46–0.96, p = 0.03; OR: 0.66, CI 95%: 0.46–0.95, p = 0.03, respectively). Conclusion: Information sources and confidence towards health professionals are the main determinants of acceptance of mandatory vaccine restoration. To increase the acceptability of the restoration and reduce vaccine hesitancy, these aspects need to be strengthened.